Characterization of a novel radiation‐induced sarcoma cell line. Issue 6 (2nd February 2015) - Lang, Julie; Zhu, Weizhu; Nokes, Brandon; Sheth, Grishma; Novak, Petr; Fuchs, Laura; Watts, George; Futscher, Bernard; Mineyev, Neal; Ring, Alexander; LeBeau, Lauren; Nagle, Ray; et al.
Abstract: Background: Radiation‐induced sarcoma (RIS) is a potential complication of cancer treatment. No widely available cell line models exist to facilitate studies of RIS. Methods: We derived a spontaneously immortalized primary human cell line, UACC‐SARC1, from a RIS. Results: Short tandem repeat (STR) profiling of UACC‐SARC1 was virtually identical to its parental tumor. Immunohistochemistry (IHC) analysis of the tumor and immunocytochemistry (ICC) analysis of UACC‐SARC1 revealed shared expression of vimentin, osteonectin, CD68, Ki67 and PTEN but tumor‐restricted expression of the histiocyte markers α1‐antitrypsin and α1‐antichymotrypsin. Karyotyping of the tumor demonstrated aneuploidy. Comparative genomic hybridization (CGH) provided direct genetic comparison between the tumor and UACC‐SARC1. Sequencing of 740 mutation hotspots revealed no mutations in UACC‐SARC1 nor in the tumor. NOD/SCID gamma mouse xenografts demonstrated tumor formation and metastasis. Clonogenicity assays demonstrated that 90% of single cells produced viable colonies. NOD/SCID gamma mice produced useful patient‐derived xenografts for orthotopic or metastatic models. Conclusion: Our novel RIS strain constitutes a useful tool for pre‐clinical studies of this rare, aggressive disease. UACC‐SARC1 is an aneuploid cell line with complex genomics lacking common oncogenes or tumor suppressor genes as drivers of its biology. The UACC‐SARC1 cell line will enable further studies of the drivers of RIS. J. Surg. Oncol. 2015 111:669–682 . © 2015 Wiley Periodicals, Inc.